2018
DOI: 10.4103/0366-6999.226893
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Profile Related with Executive Function of Chinese Preschoolers with Attention-Deficit/Hyperactivity Disorder

Abstract: Background:Previous studies have found that schoolchildren with attention-deficit/hyperactivity disorder (ADHD) showed difficulties in neuropsychological function. This study aimed to assess neuropsychological function in Chinese preschoolers with ADHD using broad neuropsychological measures and rating scales and to test whether the pattern and severity of neuropsychological weakness differed among ADHD presentations in preschool children.Methods:The 226 preschoolers (163 with ADHD and 63 controls) with the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…25 Investigations with adults born prematurely at VLBW support these findings and show that preterm birth has long-term consequences, 26 including neurocognitive deficits. 27 Specifically with relation to inhibitory control, current evidence shows that a deficit is present both in ADHD, 8,10,13,14 and in children born very prematurely. 3,28 However, to our knowledge, only one study has compared inhibitory control in VP/VLBW children with and without ADHD.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…25 Investigations with adults born prematurely at VLBW support these findings and show that preterm birth has long-term consequences, 26 including neurocognitive deficits. 27 Specifically with relation to inhibitory control, current evidence shows that a deficit is present both in ADHD, 8,10,13,14 and in children born very prematurely. 3,28 However, to our knowledge, only one study has compared inhibitory control in VP/VLBW children with and without ADHD.…”
Section: Resultsmentioning
confidence: 94%
“…11 Preschool children with ADHD tend to perform significantly worse in inhibitory control tasks and inventories, when compared to those without the disorder. [12][13][14] Although ADHD is a prevalent disorder in children born prematurely and/or at very low birth weight, only one study has compared preterm children with and without ADHD using a neuropsychological task. Both neurophysiological and neuropsychological tasks were used, and inhibitory impairments and reaction time variability were only found in preterm and term children with ADHD.…”
Section: Prematuritymentioning
confidence: 99%
“…the Flexibility Index (FI), the Inhibitory Self-Control Index, and the Emergent Metacognition Index (EMI), and a composite score, the Global Executive Composite (GEC). The higher the score is, the lower the executive function.The BRIEF-P has been shown to have adequate concurrent and discriminant validity and high reliability in Chinese children (Zhang et al, 2018).…”
Section: Behavior Rating Scale Of Executive Function-preschool Versiomentioning
confidence: 99%
“…An increasing number of studies on CU traits have focused on late childhood and adolescences (Colins and Andershed, 2015;Fanti, 2013;Fanti et al, 2017b;Fanti et al, 2013), whith little attention paid to early childhood, especially preschoolyears where early interventions can be more effective (Klingzell et al, 2016). Research has indicated that without intervention people with CU traits will have poor outcomes through out their life course (Herpers et al, 2012;2018).…”
Section: Introductionmentioning
confidence: 99%
“…Only a minority of studies in this field has focused on young children with neurodevelopmental traits. Young children with ADHD or at high risk for ADHD appear to be impaired in executive functioning [3335], while research on young children with ASD is more inconclusive [3639]. Some studies find no differences in executive functioning between children with and without ASD [38, 39], whereas others do, but depending on the different age or means of measuring executive functioning [20, 36, 37].…”
Section: Introductionmentioning
confidence: 99%